Pharmacovigilance of Drug–Drug Interactions with Nirmatrelvir/Ritonavir - Victoria Hendrick; Erast Pohorylo; Lubna Merchant; Jackie Gerhart; Iqra Naz Arham; Florin Draica; Romina Quercia; Ayman Ayoub; Reema Mehta (Infectious Diseases and Therapy)
Abstract Introduction Nirmatrelvir/ritonavir (NMV/r) is approved in the United States (US) and more than 70 other countries for the treatment of mild to moderate COVID-19 in nonhospitalized adults at high risk for severe disease. Because ritonavir inhibits several drug metabolizing enzymes, potential drug–drug interactions (DDIs) between ritonavir and concomitant medications are an important consideration for prescribers. Here, we conducted a real-world analysis of data from Pfizer’s global safety database regarding adverse events (AEs) reported during use of NMV/r concomitantly with potentially interacting drugs. Methods Data were extracted regarding DDI cases occurring from the start of NMV/r authorization through October 31, 2023. Results regarding concomitant treatment, specific AEs, and clinical outcomes are summarized. Overall NMV/r exposure was estimated based on packs of medication dispensed and was used to calculate reporting rates. Results Among 19,617,670 patients exposed globally to NMV/r, 966 cases of potential DDIs were reported. Of these, 594 occurred in the US against an estimated US exposure of 14,646,990 patients, representing a reporting rate of 0.004%. Globally and in the United States, 66.8% and 77.3% of cases, respectively, were nonserious. Simvastatin and tacrolimus were the most frequently reported drugs associated with potential DDIs, and the most frequently reported AE regarding a specific event or symptom was dysgeusia (altered sense of taste), an AE known to be associated with NMV/r. Conclusions Low reporting rates of DDIs support the potential for NMV/r treatment to be safely managed with careful use of available drug interaction resources to aid in risk mitigation.